Risk Assessment and Recommended Approaches to Optimize Infection Control and Antibiotic Stewardship to Reduce External Ventricular Drain Infection: A Single-Center Study - Jozsef Kelemen; Marton Sztermen; Eva Dakos; Gergely Agocs; Jozsef Budai; Jozsef Katona; Zsuzsanna Szekeressy; Laszlo Sipos; Zoltan Papp; Mate Bata; Janos Karczub; Mate Korompai; et al. (Antibiotics)
Background: An external ventricular drain (EVD) is used to release elevated intracranial pressure by draining cerebrospinal fluid (CSF) from the brain’s ventricles. The establishment of an EVD is one of the most commonly performed neurosurgical procedures to treat intracranial pressure in patients. Nevertheless, infections are very frequent complications. Identifying the risk factors for EVD-related infections is a key to improving patient safety and outcomes. Methods: We conducted a retrospective, single-center study of patients who underwent EVD implantation between January 2022 and March 2024. Patients were classified into infected and non-infected groups based on their clinical symptoms, as well as laboratory and microbiological results. Patient characteristics and possible risk factors for infection were compared between the two groups. Results: In total, 123 patients treated with 156 EVDs were included in this study, with a mean age of 55.8 (range: 25–84) years. EVD-associated infections were observed in 37 patients (30%). We found no significant association between infection risk and patient characteristics, including gender, primary diagnosis, craniotomy, or immunosuppression. There was no significant difference in terms of EVD insertion, i.e., whether the insertion took place in the operating room (OR) with antibiotic prophylaxis or outside the OR with no periprocedural antibiotic treatment. However, within the intensive care unit (ICU), EVD infection was much lower (13%) if EVD insertion took place in a single-bed room compared to multiple-bed room insertions (34%). Furthermore, there were significant differences in terms of the duration of first EVD (both single and multiple catheterizations) (p < 0.0001) and the total catheterization time (p = 0.0001). Additionally, there was a significant association with patient days in the ICU and EVD catheterization. Conclusions: Revisiting infection control measures is necessary, with special attention to the replacement of EVDs in single-bed ICU rooms, to introduce antibiotic prophylaxis in the ICU. Minimizing unnecessary EVD manipulation during catheterization is crucial in order to decrease the risk of EVD infection.